Forest functions and abiotic threats in private forests: conclusions from an empirical analysis of stakeholder opinions - Wysocka-Fijorek, Emilia; Gołos, Piotr; Gil, Wojciech; Sułkowska, Małgorzata; Mohytych, Vasyl (Economics and Environment, 2022)
The study aimed to recognise the preferences of various stakeholder groups representing three regions of Poland towards the most important forest ecosystem services and to determine the threats to performing these functions resulting from the occurrence of extreme weather phenomena. The study was based on surveys conducted in 2019 among various stakeholders in three regions of Poland. The respondents assigned a point weight value to each of the seven indicated forest functions and reported the occurrence of extreme weather events causing damage to forests owned or supervised by them. The survey results indicate that for all stakeholders, the most important function of the forest is timber production. However, respondents from the southern region paid more attention to water protection through forests than respondents from other regions.